Psychiatric casualties and the British counter-insurgency in Malaya. (3rd April 2022) - Probert, Thomas
ABSTRACT: The psychiatric cost of Britain's post-war counter-insurgency campaigns have gone largely un-investigated. Focusing on the Malayan Emergency, this article will show that counter-insurgency operations were sufficiently intense to produce what were conceptualised as cases of mild psychoneurosis. These conditions were managed using convalescence and simple psychotherapy. Managing these conditions in this way risked leaving more serious conditions untreated and meant recorded cases of psychoneurosis were kept artificially low. That the stresses of the counter-insurgency in Malaya were reproduced elsewhere suggests there was a wider psychiatric cost of Britain's post-war period of decolonisation.